Evaluation of hygienic conditions of food contact surfaces in retail outlets: Six years of monitoring. (April 2017) - Losito, Patrizia; Visciano, Pierina; Genualdo, Marisa; Satalino, Rosa; Migailo, Marco; Ostuni, Angelo; Luisi, Arianna; Cardone, Giorgio
Abstract: A total of 68 food contact surfaces in five different retail outlets of the following food categories: raw meat (17 surfaces), fishery products (12), deli (11), pastry (18), and dairy products (10) were monitored for hygienic conditions during the years 2010–2015. Each retail outlet was visited three times per year, except for that of dairy products which was monitored once a year. The samples were collected by hygiene swabs used on the sanitized surfaces before coming in contact with any type of food and analyzed for total aerobic count and presence of Salmonella spp. and Listeria monocytogenes . On the basis of the results, the surfaces were classified according to compliance criteria with good hygienic conditions: compliant (from not detectable to 49 CFU/cm 2 ), improvable (between 50 and 499 CFU/cm 2 ) and not compliant (>500 CFU/cm 2 ). The highest rates of improvable or not compliant data were found in the stores of raw meat (38 and 29%, respectively) and fishery products (23 and 31%), followed by deli (21 and 13%). As no regulatory limits have been established for food contact surfaces, the compliance criteria proposed in this study could be used to monitor the cleaning and sanitation procedures in the food distribution system. Highlights: Six years monitoring period of hygienic conditions of food contact surfaces. Investigation in food stores of retail outlets. Compliance criteria with hygienic conditions. Evaluation of good sanitation practices.